Modelling of Climate Risks in the Coastal Zone of Bangladesh - Ali, A M M Mostafa; Rahman, Md. Mostafizur; Hossain, Bhuiya Md. Tamim Al; Saha, Champa Rani; Nisha, Nusrath Jahan; Nelson, Katherine; Salahuddin, Ahmad (CGIAR Initiative on Asian Mega-Deltas, 2024)
Climate change is an important issue for the coastal areas around the world. The coastal areas of Bangladesh are highly vulnerable to increasing sea level, cyclonic storms and salinity intrusion. The coastal region of the country falls major victim to adverse effects of climate change owing to its geographic location, flat topography, high population density, poverty, and reliance of livelihood upon climate sensitive sectors, particularly agriculture, fisheries and water resources. The impacts of climate change are already evident in recent times with devastating cyclones such as SIDR in 2007 and AILA in 2009, exerting huge economic and social losses to the coastal Bangladesh. With this backdrop, climate risk modelling for the coastal areas of Bangladesh is essential for the protecting and maintaining the productivity of the food systems of the country.